2017
DOI: 10.3389/fnhum.2017.00246
|View full text |Cite
|
Sign up to set email alerts
|

Using Transcranial Direct Current Stimulation to Enhance Creative Cognition: Interactions between Task, Polarity, and Stimulation Site

Abstract: Creative cognition is frequently described as involving two primary processes, idea generation and idea selection. A growing body of research has used transcranial direct current stimulation (tDCS) to examine the neural mechanisms implicated in each of these processes. This literature has yielded a diverse set of findings that vary depending on the location and type (anodal, cathodal, or both) of electrical stimulation employed, as well as the task’s reliance on idea generation or idea selection. As a result, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 46 publications
2
54
1
Order By: Relevance
“…The authors 17 explained this divergent priming as a way of inducing people to adopt a particular attitude towards a creative task by visualizing themselves using an object in an unusual way. In other words, a similar creative output might be reached through both the inhibition of left inferior frontotemporal cortex (involved in inhibitory control and retention of previous experiences) 5 and the stimulation over the left DLPFC (by enhancing one's thoughts towards a specific aim under an increase in selection demands).…”
Section: Effect Of Trns On Creativity Regarding Change Scores (Seementioning
confidence: 99%
See 3 more Smart Citations
“…The authors 17 explained this divergent priming as a way of inducing people to adopt a particular attitude towards a creative task by visualizing themselves using an object in an unusual way. In other words, a similar creative output might be reached through both the inhibition of left inferior frontotemporal cortex (involved in inhibitory control and retention of previous experiences) 5 and the stimulation over the left DLPFC (by enhancing one's thoughts towards a specific aim under an increase in selection demands).…”
Section: Effect Of Trns On Creativity Regarding Change Scores (Seementioning
confidence: 99%
“…An increasing number of studies have attempted to investigate the neurological basis for creativity using either MRI 2,3 or EEG techniques 4 . Additional evidence of brain areas and networks related to creativity performance has come from studies that included noninvasive transcranial stimulation A review recently carried out by Weinberger et al 5 indicated that creative cognition may involve two main processes: idea generation (which depends on the availability of unfiltered information), and idea selection (which includes task-directed thoughts and integration of semantically distant concepts). Each of these processes has been suggested to rely primarily on different neural mechanisms 6 .More specifically, idea generation has been mostly related to cathodal Transcranial Direct Current Stimulation (tDCS) of the left inferior frontotemporal cortex, including the anterior temporal lobe 7,8 , inferior frontal gyrus 9 and prefrontal cortex 10 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…tDCS has been used for multiple health purposes [48][49][50][51][52][53]. Regarding the use of tDCS in insomnia, the role of prefronto-thalamic-cerebellar circuit on cognitive dysfunctions and sleep quality in euthymic bipolar disorder (BD) patients have showed that tDCS (2 mA) for 20 min/day during 3 consecutive weeks applied to left dorsolateral prefrontal cortex (DLPFC) and right cerebellar cortex improved sleep [54].…”
Section: Transcranial Direct Current Stimulation For Insomniamentioning
confidence: 99%